A Conceptual Study of Shatkriyakala and Its Applicability in Surgical Diseases: Life Sciences-Ayurveda - Kumar, Dr. Akshay; Dasar, Dr. Devyani; Sharma, Dr. Pariksha (International Journal of Life Science and Pharma Research, 2023)
: In Ayurveda, "shatkriyakal" sanchaya, prakopa, prasara, sthanasanshraya, vyakti, and bheda explains the causes of diseaseprogression, or its etiopathogenesis. These six stages represent the six opportunities for a doctor to treat the condition beforeit becomes severe. It is a composite expression of the words Kriya and Kala. Kriya denotes the choice of therapy (medication,diet, and daily routine) used to treat the Dosha disruption, and Kala denotes the stage of a disease’s progression. The idea ofKriyakala has been described by the ancient Indian surgeon Sushruta. Many authors have tried writing and compiling thereferences or information in classical texts. Still, there is no single article that not only compiles the textual references but alsoexplains its appropriate applied aspect or correlates its stages in the progression of surgical disorders. The present study alsotries to correlate to stages of disease progression in modern medicine with examples to show its importance today. Theobjective of this study is to review all the literature related to Shatkriyakala in classical texts of Ayurveda and compile it in asingle place to gain comprehensive knowledge about its applied aspects and make readers mind-research oriented to think ofmanagement of disease in that stage to prevent complication. The study can be used for easy referencing for conducting furtherresearch. As this review includes a step-by-step explanation and correlation of the pathogenesis of surgical diseases, there willbe an opportunity for practitioners to provide some evidence-based medicine to incept the disease in that stage to preventdisease progression and further complications.